FAKTOR-FAKTOR YANG MEMPENGARUHI RISIKO SISTEMATIS PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI DI BEJ - Zubadi, Hamron Zubadi; Wakhidaturohmah, Wakhidaturohmah (Universitas Muhammadiyah Magelang, 2005)
This research was to analyzed the factors influencing Systematic risk on Jakarta stock Exchange (JSX) during 2002-2004 observation period. The factors are dividend pay out ratio (DPR), asset Size (AS), asset Growth (AG), Leverage (LEV), liquidity (LIK), Profitability (PROF), Price to Book Value (PBV). This data research used were correct beta during 2003-2005 observation period. Secundary data taken from Indonesian Capital Market Directory (ICMD) and data base Jakarta stock Exchange Economic Faculty of UMM. Population used were all listing and active share trade on Jakarta stock Exchange amount 123 industries and the total samples obstained 30 industries. Analysis technique was multiple regression analysist with ordinary least square (OLS) with statistic and economic analysist. Finding Shows that dividend pay out ratio, and Price to Book Value (PBV) has significantly on Systematic Risk for the level less than 10%; while asset Size (AS), asset Growth (AG), Leverage (LEV), liquidity (LIK), Profitability (PROF), IS NOT SIGNIFICANT. Simultaneosuly dividend pay out ratio (DPR), while asset Size (AS), asset Growth (AG), Leverage (LEV), liquidity (LIK), Profitability (PROF), Price to Book Value (PBV), were proud that they not influenced on Systematic Risk at level less than 10%. Predicted power of those seven independent variables on Systematic Risk of 9,6%, and 80,4% others factors is not included in this models.